Challenges and Perspectives in Chemical Synthesis of Highly Hydrophobic Peptides - Mueller, Lena K.; Baumruck, Andreas C.; Zhdanova, Hanna; Tietze, Alesia A. (Frontiers in Bioengineering and Biotechnology, 2020)
Solid phase peptide synthesis (SPPS) provides the possibility to chemically synthesize peptides and proteins. Applying the method on hydrophilic structures is usually without major drawbacks but faces extreme complications when it comes to “difficult sequences”. These includes the vitally important, ubiquitously present and structurally demanding membrane proteins and their functional parts, such as ion channels, G-protein receptors, and other pore-forming structures. Standard synthetic and ligation protocols are not enough for a successful synthesis of these challenging sequences. In this review we highlight, summarize and evaluate the possibilities for synthetic production of “difficult sequences” by SPPS, native chemical ligation (NCL) and follow-up protocols.